Epigenetics: Recent Advances and Its Role in the Treatment of Alzheimer's Disease - Xiao, Xuewen; Liu, Xixi; Jiao, Bin (Frontiers in Neurology, 2020)
Objective: This review summarizes recent findings on the epigenetics of Alzheimer's disease (AD) and provides therapeutic strategies for AD. Methods: We searched the following keywords: “genetics,” “epigenetics,” “Alzheimer's disease,” “DNA methylation,” “DNA hydroxymethylation,” “histone modifications,” “non-coding RNAs,” and “therapeutic strategies” in PubMed. Results: In this review, we summarizes recent studies of epigenetics in AD, including DNA methylation/hydroxymethylation, histone modifications, and non-coding RNAs. There are no consistent results of global DNA methylation/hydroxymethylation in AD. Epigenetic genome-wide association studies show that many differentially methylated sites exist in AD. Several studies investigate the role of histone modifications in AD; for example, histone acetylation decreases, whereas H3 phosphorylation increases significantly in AD. In addition, non-coding RNAs, such as microRNA-16 and BACE1-antisense transcript (BACE1-AS), are associated with the pathology of AD. These epigenetic changes provide us with novel insights into the pathogenesis of AD and may be potential therapeutic strategies for AD. Conclusion: Epigenetics is associated with the pathogenesis of AD, including DNA methylation/hydroxymethylation, histone modifications, and non-coding RNAs, which provide potential therapeutic strategies for AD.